The Application of Using Statistical Process Control (SPC) Tools : Research Issues and Literature Review - Sarah Isniah; Humiras Hardi Purba (Universitas Ahmad Dahlan Indonesia, 2021)
A large company or industry must be able to overcome and resolve any problems that are being faced or in the future. Given that quality is the main thing that will measure the success of a company. One of the methods used in quality control is Statistical Process Control (SPC). The method to be used for this study is the study of literature. The method used is to review the 2016-2020 research papers that consistently apply the SPC method and have been published. The literature review process in this study combines published and relevant literature meta-analyses to provide some evidence of the effect of the existence of the implementation of the SPC method with several classifications. The classification includes the growth of research publications in the manufacturing sector and other sectors. The results of research literature that have been published from 2015 - 2020 is this research is useful as a basis for developing knowledge, gaps in views, providing evidence of effects, and if done well, has the capacity to be applied as further research ideas. An objective application of the SPC method can result in the elimination of waste as reduce defect and increasing quality and improving process. Subjective application of the SPC method requires high process commitment because the SPC method implements must be carried out continuously.